P0229APPLICATION OF A RISK MITIGATION STRATEGY TO PREVENT EXCESS CARDIOVASCULAR RISK IN PULMONARY HYPERTENSION: LARIAT STUDY. (6th June 2020) - White, R James; Chakinala, Murali; Chin, Melanie; Feldman, Jeremy; Goldsberry, Angie; McCullough, Peter; Meyer, Colin; O'Grady, Megan; Oudiz, Ronald; Torres, Fernando; Coyne, Daniel
Abstract: Background and Aims: Bardoxolone Methyl Evaluation in Patients with Chronic Kidney Disease and Type 2 Diabetes (BEACON) was a multinational, randomized, double-blind, placebo-controlled Phase 3 trial that enrolled patients with type 2 diabetes (T2D) and stage 4 CKD. The BEACON trial was terminated due to a significant increase in the risk of heart failure occurring within the first four weeks of treatment with bardoxolone methyl. Post-hoc analyses identified a history of heart failure and elevated baseline serum concentrations of B-type natriuretic peptide (BNP) as risk factors for these events. A subsequent study, LARIAT (NCT02316821), was designed to evaluate the efficacy and safety of bardoxolone methyl in the treatment of patients with pulmonary arterial hypertension (PAH). Progressive right heart failure is the cause of death for most PAH patients, and PAH patients are at high risk for decompensated right heart failure. LARIAT was designed to mitigate the risk for heart failure, and here we present cardiovascular safety data from this trial. Method: The LARIAT study was a 16-week double-blind, randomized, placebo-controlled, dose-ranging study that enrolled 208 patients with a confirmed diagnosis of PAH, most of whom had Group 1 Pulmonary Arterial Hypertension and were taking stable doses of at least one approved PAH therapy. Patients were randomized 3:1 to receive bardoxolone methyl or placebo at a starting dose of 2.5 mg, and subsequent doses of 5, 10, or 20mg. In addition to the dose-titration scheme, the initial protocol excluded patients with BNP > 200 pg/mL (later amended to 400 pg/mL), acutely decompensated heart failure in the previous 30 days, or eGFR < 45 mL/min/1.73 m2 at baseline. BNP and NT-proBNP were assessed serially throughout the study. In addition, 24-hour ambulatory blood pressure (ABPM) was monitored in a subset of the patients at baseline, Week 4, and Week 16. Results: One fluid overload SAE was reported in a placebo patient but not in any bardoxolone methyl patients. Overall, only 2 (1.7%) bardoxolone methyl patients reported cardiovascular SAEs, neither of which were attributed to study drug. Moreover, there were no statistically significant increases in 24-hour ABPM blood pressure, weight, or NT-Pro BNP and BNP levels in bardoxolone methyl-treated patients. Thus, treatment with bardoxolone methyl did not appear to be associated with an increased risk for heart failure hospitalizations or fluid overload adverse events in the LARIAT study. Conclusion: Despite the real risk for fluid retention and acutely decompensated heart failure in PAH patients, use of BNP < 400 pg/ml and HF history can be used to safely select patients with PAH to receive bardoxolone methyl. There was no increased risk of heart failure or other signs of overt fluid overload; we did not observe subclinical measures of fluid retention (increases in blood pressure or weight). These data support the use of a risk-mitigation strategy in the continued development of bardoxolone methyl for patients at risk for decompensated heart failure.